Rancang Bangun Aplikasi Simpan Pinjam Koperasi Pegawai Pada Komisi Yudisial RI Berbasis Android - Susi Susilowati; Hany Maria Valentine; Samuel Ramos (Eksplorasi Teknologi Enterprise & Sistem Informasi (EKSTENSI), 2022)
The Indonesian Judicial Commission Employee Cooperative in the process has several problems, namely the loan application process is still in the form of paper which is prone to loss. Cooperative members do not know whether the savings and loan application process are accepted or rejected. Then in the process of saving, borrowing, instalment and member registration transactions that cannot be accessed online. For the analysis method and the concept of this information system, the Unified Modelling Language (UML) model with the Flutter programming language and MySQL database is used. With the construction of an employee cooperative savings and loan information system at the Indonesian judicial commission, it can solve the problems faced in the company. Such as loan applications, saving, borrowing, instalment and member registration processes. This reduces work using Microsoft Excel or Word and file filling. The results obtained with the construction of this information system accelerate the savings and loan process and facilitate access to the application process.